Lipid droplet - mitochondria coupling: A novel lipid metabolism regulatory hub in diabetic nephropathy - Yang, Ming; Luo, Shilu; Yang, Jinfei; Chen, Wei; He, Liyu; Liu, Di; Zhao, Li; Wang, Xi (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is a severe lipid metabolism disorder, and ectopic lipid deposition in the kidneys aggravates DN progression. However, the molecular mechanisms underlying the renal lipid deposition in DN remain unclear. Lipid droplets (LDs) are the pools of lipids in cells that dynamically change in response to the energy requirements of the cells. A recent study reveals connections between the LDs and mitochondria, and this part of the mitochondria is called “peridroplet mitochondria (PDM).” This review summarizes the definitions, detection methods, and functions of the PDM. Finally, we discuss the research status of PDM in DN and its potential as a therapeutic target.